PENGUJIAN PECKING ORDER THEORY PADA NON-BANK FINANCIAL INSTITUTION (NBFIs) DI INDONESIA - Wardianto, Kussuyatmono Bagus (JURNAL PERSPEKTIF BISNIS, 2013)
This research investigates into the capital structure determinants of Non-Bank Financial Institutions (NBFIs) in LQ45 firms during the period of 2004-2011. For this purpose, leverage is taken as dependent variable while tangibility, growth, size andÂ profitability are selected as independent variables. The study has shown thatÂ tangibility and profitability are significant in explaining variation in leverage of the NBFIs in LQ45 firms while growth and size are insignificant in explaining variation in leverage of the NBFIs in LQ45 firms.Keywords: Leverage, tangibility, growth, size,Â profitability, pecking order theory.